Dziedziczne podłoże czerniaka - wyniki badań własnych na tle piśmiennictwa - Tadeusz Dębniak; Romuald Maleszka; Jan Lubiński (Termedia Publishing House, 2011)
Malignant melanoma (MM) represents one of the most aggressive neoplasmsand its frequency is rapidly increasing. Familial aggregations ofthis malignancy are present in around 3-15% of all cases. CDKN2A isthe major "high-risk" MM susceptibility gene. Recently new selectioncriteria for CDKN2A genetic assessment of patients - the so-called mnemonic"guideline of three" - have been proposed: 1) individuals withthree or more primary melanomas, 2) three or more melanomas amongfirst or second degree relatives, 3) presence of three or more cases ofmelanoma and/or pancreatic cancer on the same side of the family. Inthe Polish population a common CDKN2A variant (A148T) significannowotlyincreases melanoma risk regardless of the cancer family history.A recent multi-centre genome-wide association study identified threeloci strongly associated with melanoma risk: 16q24, 11q14-q21, 9p21.The list of mutations/polymorphisms which are believed to be associatedwith moderate MM risk includes: Lys751Gln_CC/Gly156Gly_CC ofthe XPD gene; R151C, V60L, R160C, R163Q of the MC1R gene; N991Dof the BRCA2 gene and haplotype rs731236_A + rs1544410_T of theVDR gene. Appropriate management may reduce morbidity and mortality.Genetic testing and clinical evaluation should be performed, andfamily history should be obtained in all patients affected with MM, includingthose with apparently sporadic tumours.